2007
DOI: 10.1186/1748-5908-2-16
|View full text |Cite
|
Sign up to set email alerts
|

Primary care provider preferences for working with a collaborative support team

Abstract: Background: Clinical interventions based on collaborative models require effective communication between primary care providers (PCPs) and collaborative support teams. Despite growing interest in collaborative care, we have identified no published studies describing how PCPs prefer to communicate and interact with collaborative support teams. This manuscript examines the communication and interaction preferences of PCPs participating in an ongoing randomized clinical trial of a collaborative intervention for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Characteristics such as physician communication style, 42,43 better organizational climate, 44,45 and systematic improvements in practice access 46 are reported to promote efficiency and/or quality. We need to better understand what makes some practices high performing and what factors support greater efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics such as physician communication style, 42,43 better organizational climate, 44,45 and systematic improvements in practice access 46 are reported to promote efficiency and/or quality. We need to better understand what makes some practices high performing and what factors support greater efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…These sessions introduced the intervention, included education about chronic pain and abbreviated training in shared decisionmaking skills, 31 and surveyed clinicians' communication preferences. 32 After enrolling in the study, intervention patients received an initial telephone contact, were mailed written materials, and received an assessment visit with the care manager. Assessments were usually performed face-to-face in primary care clinics but occasionally by telephone or videoconferencing.…”
Section: Interventionmentioning
confidence: 99%
“…Several studies have suggested that practice issues such as time constraints, a lack of access to a mental health specialist, and a lack of training and experience significantly increase clinicians' levels of discomfort when working with patients with depression (Bower & Rowland, 2006; Dobscha, Leibowitz, Flores, Doak, & Gerity, 2007; Hull, Jones, Tissier, Eldridge, & Maclaren, 2002; Meredith et al, 1999; Nutting et al, 2002; Onate, 2006; Sigel & Leiper, 2004; Starfield, Forest, Nutting, & von Schrader, 2002; Telford, Hutchinson, Rix, & Howe, 2002).…”
mentioning
confidence: 99%